Stent implantation in severe aortic coarctation in a pediatric patient with Turner syndrome: Case report and literature review - Yuese Lin; Yuese Lin; Ling Zhu; Ling Zhu; Xuandi Li; Xuandi Li; Hongjun Ba; Hongjun Ba; Xiufang He; Xiufang He; Shujuan Li; Shujuan Li (Frontiers Media S.A., 2023)
BackgroundTurner syndrome is a rare systemic disease and a significant proportion of these patients experience aortic coarctation. Selection of optimal therapy for aortic coarctation in patients with Turner syndrome is difficult due to the pathologic change of the systemic vessel.Case presentationWe report one successful case of covered stent implantation for the treatment of severe native coarctation of the aorta in a 15-year-old patient with Turner syndrome weighing 36 kg. A covered stent was implanted in this patient. After the stent implantation, the peak systolic pressure gradient immediately decreased from 48 mmHg to 14 mmHg. The aortic diameter at the coarctation site increased from 3 mm to 10 mm after stenting. A femoral arterial complication occurred in this case, and we stabilized the situation finally.ResultsDuring a follow-up of 3 years, no restenosis of aortic coarctation was observed and the patient no longer experienced hypertension. The dissection of the right femoral artery remained stable.ConclusionA covered stent implantation for severe aortic coarctation in patients with Turner syndrome could be safe and effective. However, caution should be taken when using the technique to prevent complications.